Interactive association between RhoA transcriptional signaling inhibitor, CCG1423 and human serum albumin: Biophysical and in silico studies - Kabir, Md Zahirul; Ghani, Hamidah; Mohamad, Saharuddin; Alias, Zazali; Tayyab, Saad (Taylor & Francis, 2018)
Multiple spectroscopic techniques, such as fluorescence, absorption, and circular dichroism along with in silico studies were used to characterize the binding of a potent inhibitor molecule, CCG1423 to the major transport protein, human serum albumin (HSA). Fluorescence and absorption spectroscopic results confirmed CCG1423–HSA complex formation. A strong binding affinity stabilized the CCG1423–HSA complex, as evident from the values of the binding constant (Ka = 1.35 × 106–5.43 × 105 M−1). The KSV values for CCG1423–HSA system were inversely correlated with temperature, suggesting the involvement of static quenching mechanism. Thermodynamic data anticipated that CCG1423–HSA complexation was mainly driven by hydrophobic and van der Waals forces as well as hydrogen bonds. In silico analysis also supported these results. Three-dimensional fluorescence and circular dichroism spectral analysis suggested microenvironmental perturbations around protein fluorophores and structural (secondary and tertiary) changes in the protein upon CCG1423 binding. CCG1423 binding to HSA also showed some protection against thermal denaturation. Site-specific marker-induced displacement results revealed CCG1423 binding to Sudlow’s site I of HSA, which was also confirmed by the computational results. A few common ions were also found to interfere with the CCG1423–HSA interaction.